(untitled) (Journal of Monno Medical College, 2026)
Background: Generalized Anxiety Disorder (GAD) is such a psychiatric disorder where some specific somatic symptoms are prerequisite to confirm the diagnosis. Objective: This study was aimed at assessing somatic complaints reported by Generalized Anxiety Disorder (GAD) patients during treatment seeking in Bangladesh. Methodology: This cross-sectional survey design using purposive sampling technique was carried out in two psychiatric settings of Manikganj district from January, 2024 to December 2024. Data were collected by a psychiatrist who confirmed the diagnosis of GAD following the diagnostic criteria of Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5). Only adult GAD patients who provided consent to participate were included in this study. Ethics to conduct study with human participants were maintained strictly. Results: 228 participants with age range of 18-75 participated in this study in which most of the participants were female, married, and from rural areas. Somatic complaints reported by the participants while consulting with a psychiatrist can be categorized in three types: (i) head related complaints (ii) gastrointestinal complaints and (iii) palpitations. Head related complaints were Hotness in the head (84.65%), Headache (69.73%), burning sensation in the head (60.96%), heaviness in the head (25.44%), uneasiness in the head (20.61%) and vertigo (19.74%). Reported gastrointestinal complaints by the participants were- lack of appetite (35.96%), gas formation (26.32%), constipation (16.23%) and vomiting (13.16%). Palpitations were also reported by 18.42% participants. Conclusion: Somatic complaints identified in this study will guide physicians and mental health professionals not only to ensure early diagnosis but also to provide appropriate treatment towards GAD patients of Bangladesh. Journal of Monno Medical College, June, 2025; 11(1) : 18-22